2019
DOI: 10.15537/smj.2019.1.22919
|View full text |Cite
|
Sign up to set email alerts
|

Systematic psychiatric assessment of patients with sickle cell disease

Abstract: Objectives: To determine the level of the psychological problems such as depression and anxiety in sickle cell disease (SCD) patients in Tabuk region, northwestern Saudi Arabia. Methods: In this cross-sectional study, 89 patients with SCD was assessed in the outpatient clinics of King Salman Armed Forces Hospital, Tabuk, Saudi Arabia between March 2017 and August 2017. Two validated Arabic translated questionnaires, the Patient Health Questionnaire (PHQ-9) and the Gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
7
2
1
Order By: Relevance
“…According to the depression categories and based on the cutoff, the depression rate was 45.4%, which was represented by the (moderate-moderately severe-severe) depression categories; however, the nondepressed is a little higher (54.1%) than depressed patients, which is represented by (nondepressed-mild) depression categories. These findings were compatible with a study conducted in Tabuk that reported a depression rate was 36% and nondepressed SCD patients were 64% [ 11 ]. Furthermore, we found that the rate of anxiety in our study was 22.7%, which was less than that reported by Tabuk and Levenson et al [ 11 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…According to the depression categories and based on the cutoff, the depression rate was 45.4%, which was represented by the (moderate-moderately severe-severe) depression categories; however, the nondepressed is a little higher (54.1%) than depressed patients, which is represented by (nondepressed-mild) depression categories. These findings were compatible with a study conducted in Tabuk that reported a depression rate was 36% and nondepressed SCD patients were 64% [ 11 ]. Furthermore, we found that the rate of anxiety in our study was 22.7%, which was less than that reported by Tabuk and Levenson et al [ 11 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…These findings were compatible with a study conducted in Tabuk that reported a depression rate was 36% and nondepressed SCD patients were 64% [ 11 ]. Furthermore, we found that the rate of anxiety in our study was 22.7%, which was less than that reported by Tabuk and Levenson et al [ 11 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, it seems that the presence of chronic diseases does not explain the higher odds of depression observed in this study compared to those with lower percentages of chronic diseases. In addition, the rate of depression in MG patients in this study is comparable to the rate of depression among Saudi patients with sickle cell disease and gastrointestinal disorders [24, 25], but significantly less than that among patients with hematological malignancies and multiple sclerosis [26, 27].…”
Section: Discussionsupporting
confidence: 54%
“…We cannot deduce from these results the percentage of patients suffering from psychological disorders. In other studies, the proportion of SCD patients reporting psychological disturbances was very variable: 18 to 62% for depressive symptoms and 7 to 67% for anxiety symptoms [26,[49][50][51][52].…”
Section: Medication and Psychoactive Substances Usementioning
confidence: 78%